1944
DOI: 10.1084/jem.79.2.137
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Chemical Nature of the Substance Inducing Transformation of Pneumococcal Types

Abstract: Biologists have long attempted by chemical means to induce in higher organisms predictable and specific changes which thereafter could be transmitted in series as hereditary characters. Among microSrganisms the most striking example of inheritable and specific alterations in cell structure and function that can be experimentally induced and are reproducible under well defined and adequately controlled conditions is the transformation of specific types of Pneumococcus. This phenomenon was first described by Gri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
373
0
9

Year Published

1944
1944
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,801 publications
(392 citation statements)
references
References 14 publications
2
373
0
9
Order By: Relevance
“…Besides potentially limiting diffusion of the fluorescent proteins by localizing them to the nucleoid (see below), we have shown previously by highthroughput sequencing of RNA transcripts (RNA-Seq) that hlpA is highly transcribed (40). The fusion constructs were integrated into the pathogenic encapsulated S. pneumoniae D39 genetic background (41), resulting in strains JWV500 (HlpA-GFP) and MK119 (HlpA-RFP) (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Besides potentially limiting diffusion of the fluorescent proteins by localizing them to the nucleoid (see below), we have shown previously by highthroughput sequencing of RNA transcripts (RNA-Seq) that hlpA is highly transcribed (40). The fusion constructs were integrated into the pathogenic encapsulated S. pneumoniae D39 genetic background (41), resulting in strains JWV500 (HlpA-GFP) and MK119 (HlpA-RFP) (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…We have since come to recognize that DNA is the genetic material containing all the information essential for life and the basis for heredity (2). The human genome is divided into 46 DNA molecules, or chromosomes, consisting of pairs of chromosomes 1 to 22 (autosomes), numbered sequentially according to their size, and of two sex chromosomes that determine whether an individual is male or female (Fig.…”
mentioning
confidence: 99%
“…The bacterial strains (Escherichia coli and S. pneumoniae) and plasmids used in this study are shown in Table 1. Encapsulated S. pneumoniae D39 (serotype 2; NCTC7466) (22) and WU2 (serotype 3) (23) strains and their isogenic ⌬adhE (serotype 2 and 3), ⌬rex (serotype 2), and ⌬spxB (serotype 2) mutants were used. The mutants were created using an ermB cassette inserted opposite to the target gene orientation to disrupt its expression (24).…”
mentioning
confidence: 99%